The Combination of British Parliamentary Debate and Peer Assessment in Teaching Speaking - Asriadi Rasyid; Rafiah Nur; Ammang Latifa; Rahmatullah Syaripuddin; Kasmawati Kasmawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The main problems of this research were how to improve the speaking ability of EFL students converting grammar, vocabulary, pronunciation, discourse, and strategies. therefore, how to encourage them to use English.  This research aimed to see whether the combination of British Parliamentary Debate and Peer Assessment may enhance the speaking ability of EFL students. A quasi-experimental method with non-equivalent group design was carried out in this research. The population was the third semester of English Department students at Universitas Muhammadiyah Parepare. Two classes from the population, representing the experimental class and the control class, were selected using the cluster random selection technique as the study's sample. This research used an interview test with a variety of themes as its instrument. Pre-test, treatment, and post-test were the three steps that made up the data collection processes. The data that obtained by the test were then submitted to a quantitative analysis. The research findings demonstrate that the experimental class students' speaking abilities were better to those of the control class. The data from the experimental class showed that the students' mean score was higher compared to the control class (59,68 > 49,06). In conclusion, the combination of British Parliamentary Debate and Peer Assessment was improved the students’ speaking ability.